The longitudinal effects of education on depression: Finding from the Indonesian national survey - Patria, Bhina (Frontiers in Public Health, 2022)
A thorough and continuous investigation of the association between education and depression in Southeast Asia is critical, particularly in Indonesia, where depression is highly prevalent. Despite this, studies on education and depression mainly use a cross-sectional design alone, which cannot control the bidirectionality of the relationship. Therefore, this study investigated the longitudinal effects of education on depression symptoms, based on nationally representative survey data. This study used as its basis a longitudinal socioeconomic and health survey in Indonesia, the Indonesia Family Life Survey (IFLS). The survey collected data through face-to-face interviews with individual respondents and their families. The fourth and fifth waves of IFLS datasets were used in the analysis. A total number of 18,374 adult participants were included in the dataset. Depression symptoms were assessed based on a 10-item version of the CES-D (Center for Epidemiologic Studies Depression) Scale. Education level was the highest level of education attained by the participants. A cross-lagged longitudinal model was tested using structural equation modeling (SEM) or analysis of covariance structure. The results showed that the model of education and depression fits the data well. The fit indices of the model, Chi2 (1, N =18374) = 21.592, p = .001, RMSEA = .033, CFI = .999, fulfilled the requirements for a good fit. Meanwhile, further analysis of the cross-lagged model revealed that education predicted depression and not the other way around. The standardized regression weights showed that higher education attainment reduces the risk of depression later in life. This study asserts that educational attainment has longitudinal effects on depression. Therefore, expanding the policies surrounding educational opportunity may prevent the onset of depression. This is important, especially in the Indonesian context, where the prevalence of depression among adults is higher than the global average. Access to further education deserves continued consideration in research and policy discussions on mental health and educational system development.